Experiment of microfluidic chip for biomolecule sensing - Tong, Wilson Wei Jie (2018)
This final year project report is about the study of photonic sensing of the bacteria, E. coli, through a process called fluorescence intensity test. UV-light is shined onto the sample to see if there was any emission light under the microscope to indicate the presence of E. coli. Moreover, the design and fabrication of microfluidic chip to reduce the sample requires and shorten the time taken for detection. The chips were made of either acrylic or silicone. After further test are carried out, silicone chips proved to be better compared to acrylic and hence was met for this final year project. The chips were loaded with different samples of E. Coli using a syringe pump. After ensuring that sample were fully loaded into the chips with no air bubbles in it, it was then place under a microscope to expose to UV light to check for any E. Coli in the chip. This technique was shown to reduce the sample required as well as the time taken to detect the E. Coli in the sample.